THE SUPERVISORY PERFORMANCE OF BAWASLU HULU SUNGAI UTARA IN THE 2019 ELECTION - Febriadi, Herry (Scholar Center, 2021)
The Hulu Sungai Utara Regency Election Supervisory Body is an Election organizing body tasked with overseeing the implementation of Elections, the problem is the improper installation and / or distribution of Campaign Props (Campaign), Campaign Materials (BK), Unclear division of labor. The purpose of this study was to determine the Performance of the Election Oversight Body in the Supervision of Election of the House of Representatives, Members of the Regional Representative Council, President and Vice President in 2019 at the Election Supervisory Body (Bawaslu) of North Hulu Sungai Regency and the factors that influence it. This research uses a qualitative approach with descriptive-qualitative type. Data collection techniques used were interviews, observation and documentation. Source of data taken through a purposive withdrawal of 15 people. After the data is collected, it is then analyzed using techniques including data reduction, data presentation, and data verification or drawing conclusions. Test the credibility of the data in this study is the extension of observation, increase perseverance, triangulation, negative case analysis, and hold a member check. The results of the research on the performance of the Election Oversight Body in the Supervision of the Election of the House of Representatives, Members of the Regional Representative Council, the President and Vice President in 2019 on the Election Supervisory Body (Bawaslu) of North Hulu Sungai Regency have not been good this can be seen from several indicators.